Pembelajaran Berbasis Proyek Pada Mata Pelajaran Aqidah Akhlak Kelas X di MA Al-Fatah - Abdul Ghofar, Abdul; Muawanatul Hiftiroh , Mia (Amaliyatu Tadris, 2022)
This study aims to increase student’s creativity and interest in student’s talent in the Aqidah Akhlak class X at MA AL-Fattah trough project-based Learning. This research uses descrptive-qualitative. data collection is done by observation, interviews, documentation. The Sources of data ini this study i obtained form student and teachers at MA Al-Fatah.. The results of project-based learning are shown by increasing student interest and creativity before and aftter the implementation of this learning project to make comics, so that stundents understand more about the Disgraceful morals material in depth.